The Karavansalija Mineralized Center at the Rogozna Mountains in SW Serbia: Magma Evolution and Time Relationship of Intrusive Events and Skarn Au ± Cu–Pb–Zn Mineralization - Hoerler, J.; Von Quadt, A.; Burkhard, R.; Peytcheva, I.; Cvetkovic, V.; Baker, T. (Frontiers in Earth Science, 2022)
The Karavansalija Mineralized Center (KMC) with its Au-Cu skarn mineralization in southwestern Serbia belongs to the Oligocene Serbo-Macedonian-Magmatic and Metallogenic Belt. Samples from intrusive and volcanic rocks at the KMC show typical arc signatures of subduction derived magmas through enrichment in large ion lithophile elements (LILE) and depletion of high field strength elements (HFSE). The magmas developed a high-K (calc-alkaline) fractionation trend and evolved towards shoshonitic compositions. Zircon LA-ICP-MS and high-precision CA-ID-TIMS dating together with zircon trace element and Hf isotope measurements were carried out to couple the geochronologic and geochemical evolution. The results suggest, that magmatism starts around 29.34 Ma with subvolcanic intrusions followed by a more evolved magmatic intrusion that was emplaced into Cretaceous limestone, generating a widespread skarn alteration at 28.96 Ma. After a period of quiescence of about 1.2 Ma, either another magma body evolved, or the same upper crustal magma chamber was recharged and also partly re-activated older plutonic rocks as indicated by xenocrysts. The REE ratios shift from apatite, titanite ± amphibole dominated fractionation of the older magmatic event to crystallization of allanite, efficiently depleting the LREE and Th/U in the younger upper crustal magma. After a lamproite-like melt was injected, the increased heat and fluid pressure lead to the expulsion of a quartz-monzonite porphyritic stock at ca. 27.72 Ma, strongly interacting with the skarns and established a fertile hydrothermal system. Soon after a non-mineralized second pulse of porphyry some dykes cut the previous phenocryst-rich “crowded” porphyries and skarns at ca. 27.60 Ma, thus bracketing the maximum timespan of ore mineralization to about 112 ± 45 Ka. Increased contribution of a lamproite-like melt is inferred from the presence of phlogopite micro-phenocrysts, phlogopitization of biotite and diopside clusters in the latest porphyry dykes. There is a trend of increased crustal assimilation from the oldest volcanic phase to the emplacement of the youngest porphyry dykes recorded by ɛ-Hf of the zircons. Oligocene occurrences of significant base metal mineralization within Serbia, Northern Macedonia and Greece e.g., Crnac, Rudnik, Veliki Majdan, Stratoniu or the Cu- Au porphyry at Buchim (Northern Macedonia) are all associated with trachy-andesitic porphyry dykes.